Translational Perspectives on the Therapeutic Potential of Hyptis Crenata Essential Oil Terpenes in Smooth Muscle Function - Cardeal dos Santos, André Nogueira; da Cruz Freire, José Ednésio; Rodrigues, Bruna Ferreira; Ferreira-da-Silva, Francisco Walber; Júnior, José Eduardo Ribeiro Honório; Leal Cardoso, José Henrique; de Souza, Andrelina Noronha Coelho (Planta Medica, 2024)
Monoterpenes and sesquiterpenes are classes of organic compounds found in various natural products, such as the essential oil of Hyptis crenata (EOHc). The therapeutic potential of these terpenes present in EOHc is evidenced by their effect on smooth muscle and potential clinical applications. Among the highlighted monoterpenes, such as sabinene, α-pinene, and β-pinene, a relaxing effect on rat intestinal smooth muscles is observed, attributed to interaction with calcium channels. Furthermore, monoterpenoids like borneol, cineole, and linalool also demonstrate vasorelaxant properties, suggesting potential in the treatment of cardiovascular conditions. Sesquiterpenes, such as caryophyllene and aromadendrenes, exhibit relaxing effects in various smooth muscle tissues, such as rat uterus and guinea pig ileum, indicating pharmacological potential in these areas. The translational exploration of targets, such as calcium channels and G protein-coupled receptors, highlights the importance of these compounds in discovering new therapies based on natural products for treating various medical conditions.
Keywords: Hyptis crenata; Lamiaceae; monoterpenes and sesquiterpenes; effect on smooth muscle; biomedical applications